Meningkatkan Kemampuan Kosakata Bahasa Inggris Melalui Permainan Kata Berantai - Rahma, Umniatul; Ariyani, Amra; K, Mercy Sumakul (Indonesian Journal of Pedagogical and Social Sciences, 2023)
Abstract. This research aimed to examine the application of the word chain game learning technique in improving students' English vocabulary skills. This research also intends to increase students' self-confidence and courage to speak in English, especially in XI MIPA 2, SMA Negeri 14 Makassar. This form of research is included in the form of descriptive research with a quantitative approach. This research uses a chain word game technique. This research is included in the type of classroom action research which consists of two cycles. Data collection techniques used are observation and tests. Quantitative data obtained from the test in the form of students' vocabulary scores were analyzed using the Excel program to find out the average score obtained from the results of the students' vocabulary test by comparing the scores obtained before and after the action was given. The results of this research showed that the English vocabulary skills of students in class XI MIPA 2 SMA Negeri 14 Makassar experienced an increase after the word chain game technique was applied to learning English. This can be seen from the average score of each cycle which continues to increase, from pre cycle to cycle I increased by 22%, this can be seen from the average score of 58 to 80 and from cycle I to cycle II increased by 10%, it also can be seen from an average score of 80 to 90. Based on these results, it can be concluded that the application of chain word games can improve students' vocabulary skills in English subjects. Learning English using the chain word game technique has also succeeded in making students more active and also more enthusiastic in learning English because they already have high confidence in making English sentences. Keywords: Vocabulary, Chain Word Game, English